Pemanfataan Aplikasi Canva Sebagai Media Desain Promosi Produk Bagi Guru SDN 18 Kampung Durian - Juli Adevia; Nova Suryani; Oza Syafriani; Defri Rahman; Muhammad Ilham; Ahmad Fachri; Muhammad Farrasky Delas Putra; Yozi Putri Sakinah; Sultani Sultani; Ramadhi Ramadhi; Barkhia Yunas; Oktia Verinda; Allia Nabila (Universitas 45 Surabaya, 2024)
The community service program titled